Performance and Emission Analysis of Piston Bowl Type and Depth Variations on Diesel Engine Shark R180 - Fathin Muhammad Mahdhudhu; Agung Dwi Priono; Shadinty Azhar Sausan; James Julian; Elvi Armadani; Riki Hendra Purba; Fitri Wahyuni (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2026)
The performance and emission study on the different types of piston bowls and the depth variation of the piston bowl is discussed in this paper. Simulations were conducted using the open-source software, Diesel-RK. Three models of piston bowls and five variations of piston depth were used to estimate performance and emissions. The type of fuel and engine operating conditions were set to be constant. The performance responses consist of power, Specific Fuel Consumption (SFC), and brake mean effective pressure (BMEP). On the other hand, the emissions of NOx and Particulate matter (PM) were analyzed. Results show that both power response and BMEP improve with an increase in piston depth across all types of piston bowls. On the contrary, the SFC trend line shows a decline as piston depth increases. For the emissions, NOx experiences a rising trend as the depth of the piston bowl increases at all types of piston bowls. Conversely, the particulate matter (PM) trend is decreasing as the depth of the piston bowl increases.